UPAYA MENINGKATKAN PRESTASI BELAJAR IPA SISWA KELAS IV SDI NGALUPOLO ENDE DENGAN METODE PENEMUAN TERBIMBING - Natalia Pankrasia (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Every elementary school student has a high curiosity. Therefore, this curiosity must continue to be fostered in science learning. However, it was found that the fourth grade students of SDI Ngalupolo did not show good science learning outcomes. Students' curiosity needs to be used in learning by using the guided discovery method so that science learning achievement can be improved. The purpose of this study was to improve the science learning achievement of Class IV SDI Ngalupolo students using guided discovery learning through classroom action research (CAR). CAR is carried out in 3 cycles where each cycle consists of planning, implementation, evaluation and reflection. Data were collected using teacher observation sheets, student observation sheets and tests. The results showed that student achievement increased from cycle I to cycle III, namely, cycle I (63.75%), cycle II (70%), cycle III (80%). Thus the guided discovery learning method can improve the learning achievement of Class IV SDI Ngalupolo students.